State building in Putin's Russia policing and coercion after communism - Taylor, Brian D., 1964- (Cambridge University Press, 2011)
"Building a strong Russian state was the central goal of Vladimir Putin's presidency. This book argues that Putin's strategy for rebuilding the state was fundamentally flawed. Taylor demonstrates that a disregard for the way state officials behave toward citizens--state quality--had a negative impact on what the state could do--state capacity. Focusing on those organizations that control state coercion, what Russians call the "power ministries," Taylor shows that many of the weaknesses of the Russian state that existed under Boris Yeltsin persisted under Putin. Drawing on extensive field research and interviews, as well as a wide range of comparative data, the book reveals the practices and norms that guide the behavior of Russian power ministry officials (the so-called siloviki), especially law enforcement personnel. By examining siloviki behavior from the Kremlin down to the street level, State building in Putin's Russia uncovers the who, where, and how of Russian state building after communism"--Provided by publisher.